Prognostic factors for streptococcal toxic shock syndrome: systematic review and meta-analysis. Issue 12 (1st December 2022) - Bartoszko, Jessica J; Elias, Zeyad; Rudziak, Paulina; Lo, Carson K L; Thabane, Lehana; Mertz, Dominik; Loeb, Mark
Abstract : Objectives: To quantify the prognostic effects of demographic and modifiable factors in streptococcal toxic shock syndrome (STSS). Design: Systematic review and meta-analysis. Data sources: MEDLINE, EMBASE and CINAHL from inception to 19 September 2022, along with citations of included studies. Eligibility criteria: Pairs of reviewers independently screened potentially eligible studies of patients with Group A Streptococcus -induced STSS that quantified the association between at least one prognostic factor and outcome of interest. Data extraction and synthesis: We performed random-effects meta-analysis after duplicate data extraction and risk of bias assessments. We rated the certainty of evidence using the Grading of Recommendations, Assessment, Development and Evaluation approach. Results: One randomised trial and 40 observational studies were eligible (n=1918 patients). We found a statistically significant association between clindamycin treatment and mortality (n=144; OR 0.14, 95% CI 0.06 to 0.37), but the certainty of evidence was low. Within clindamycin-treated STSS patients, we found a statistically significant association between intravenous Ig treatment and mortality (n=188; OR 0.34, 95% CI 0.15 to 0.75), but the certainty of evidence was also low. The odds of mortality may increase in patients ≥65 years when compared with patients 18–64 years (n=396; OR 2.37, 95% CI 1.47 to 3.84), but the certainty of evidence was low. We are uncertain whether non-steroidal anti-inflammatory drugs increase the odds of mortality (n=50; OR 4.14, 95% CI 1.13 to 15.14; very low certainty). Results failed to show a significant association between any other prognostic factor and outcome combination (very low to low certainty evidence) and no studies quantified the association between a prognostic factor and morbidity post-infection in STSS survivors. Conclusions: Treatment with clindamycin and within clindamycin-treated patients, IVIG, was each significantly associated with mortality, but the certainty of evidence was low. Future research should focus on morbidity post-infection in STSS survivors. PROSPERO registration number: CRD42020166961.